Acquiring L2 phonology: foreign accent and L1 influence - Salheen, Dalal Alfadhil Attaher; Yap, Ngee Thai (Human Resource Management Academic Research Society, 2023)
Acquiring another language is a fairly challenging process. Pronunciation is one of the language components which embodies a source of concern for many learners. The reason behind this concern is that English has many difficult sounds for non-native speakers. As an English learner, improving pronunciation can help not only in making natural sentences, but also in making the speech clear and understandable. This work is trying to shed light on the process of acquiring L2 phonology; how it occurs, and what factors could affect the perception of L2 speech sounds. Also, the paper discusses the concept of foreign accent and how this phenomenon influences speech perception, i.e., how accurately the speech is perceived when spoken from a non-native English speaker. Further, the paper argues the impact of accent variation on the intelligibility level of the English spoken language with highlighting the accent-intelligibility relationship, which is considered as a crucial in many, many different spheres.